The use of non-steroidal anti-inflammatory drugs in cerebrovascular diseases - Demir, Caner Feyzi; Tasci, Irem (Nova Science Publishers, Inc., 2021)
Cerebrovascular diseases (CVD) are a group of diseases resulting from ischemic or hemorrhagic conditions, causing neurological deficits. In developed countries, CVD are the third leading cause of death and the leading cause of disability. In ischemic and hemorrhagic conditions, nonsteroidal and anti-inflammatory drugs (NSAIDs) are commonly used as antiplatelet, anti-inflammatory, and analgesic drugs. On the other hand, these drugs have been associated with increased risk of hemorrhage and thrombosis. One of cyclooxygenase-1 (COX-1) inhibitor, acetylsalicylic acid (ASA), is the most widely used agent in the acute treatment and prophylaxis of ischemic CVD. Moreover, ASA catalyzes the conversion of arachidonic acid into prostaglandin H2 through irreversible acetylation of COX-1 and cyclooxygenase-2 (COX-2), thereby reducing platelet aggregation. Another subgroup of NSAID is known as COX-2 selective NSAIDs including celecoxib, rofecoxib, and valdecoxib. These agents, however, have been removed from the market after being reported to increase the incidence of thrombotic stroke and myocardial infarction. A previous meta-analysis indicated that diclofenac, similar to coxibs, increases the risk of ischemic CVD compared to the nonuse of NSAIDs and also suggested that naproxen appears to have a better CVD safety profile compared to other NSAIDs. As NSAIDs are a chemically heterogeneous group of compounds, the use of each compound may have a different effect on not only thrombotic but also hemorrhagic risk factors. A recent study conducted systematic review to evaluate the risk of CVD associated with the use of individual NSAIDs and revealed that the use of diclofenac and meloxicam is associated with an increased risk of hemorrhagic CVD. The authors also noted that the use of these two NSAIDs leads to vasoconstriction by inhibiting the COX-2 in the kidney and also increases salt and water reabsorption, thereby increasing the risk of hypertension and CVD. In light of these notions, it is safe to assert that when prescribing NSAIDs, these drugs may have procoagulant effects, cause hypertension by increasing fluid and salt retention, may interact with drugs used in CVD prophylaxis. So it should be recognized that these drugs are likely to cause an increased risk of thrombosis and hemorrhage. © 2021 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Cyclooxygenase-1; Cyclooxygenase-2; Hemorrhagic stroke; Inhibitor; Ischemic stroke